Manajemen Mutu Madrasah Diniyah dalam Lanskap Pendidikan Islam Nonformal: Analisis Sistematis atas Prinsip, Implementasi, dan Tantangan - Putri Kurniawati; As’aril Muhajir; Agus Zaenul Fitri (J-MPI (Jurnal Manajemen Pendidikan Islam), 2025)
Quality management is a strategic element in the management of educational institutions, including Madrasah Diniyah which has unique characteristics as a non-formal religious institution. This research aims to examine the basic principles, implementation practices, and challenges faced in implementing quality management. The method used is Systematic Literature Review (SLR) following the PRISMA stages. Articles obtained from Google Scholar via Publish or Perish with a range of 2020–2025. Of the 100 articles identified, 50 were selected based on inclusion and relevance criteria, and 15 articles met quality appraisal for analysis. The results of this research show that the principles in quality management at Madrasah Diniyah are customer focus, continuous improvement, scientific approach, inclusiveness and moderation. The stage of implementing quality management at Islamic schools includes curriculum development that integrates religious education and practical skills, teacher professional development, community involvement, internal quality assurance, and resource management. As well as the challenges faced in quality management of Islamic madrasas, namely limited resources, curriculum problems, teacher quality, community participation. The limitations of this research lie in the literature sources which only come from Google Scholar within a certain time period and are not accompanied by direct field verification, so the findings obtained still require strengthening through further empirical research.